Electrochemical performance and stability of cobalt-free Ln1.2Sr0.8NiO4 (Ln=La and Pr) air electrodes for proton-conducting reversible solid oxide cells. (20th March 2018) - Yang, Shaojing; Wen, Yabing; Zhang, Jingchao; Lu, Yang; Ye, Xiaofeng; Wen, Zhaoyin
Abstract: Cobalt-free Ruddlesden-Popper structured Ln1.2 Sr0.8 NiO4 (Ln = La and Pr) have been synthesized by a modified Pechini method, moreover, their thermal and electrochemical properties as well as performance of cells with proton-conducting electrolytes have been investigated. Experimental results reveal that the thermal expansion coefficients of Ln1.2 Sr0.8 NiO4 are close to those of Ba(Ce, Zr)O3 -based proton conductors. The polarization resistances of symmetrical cells with La1.2 Sr0.8 NiO4 (LSN) and Pr1.2 Sr0.8 NiO4 (PSN) electrodes are as low as 0.15 and 0.23 Ω cm 2 at 700 °C, respectively. Besides, Ln1.2 Sr0.8 NiO4 can remain stable structure over 100 h in humidified air (20 vol% H2 O) at 800 °C. Furthermore, proton-conducting reversible solid oxide cells (PC-RSOCs) with LSN and PSN air electrodes exhibit maximum power densities of 0.46 and 0.35 W cm −2 in solid oxide fuel cell mode at 700 °C, respectively. Meanwhile, the same cells achieve current densities as high as 1.37 and 1.12 A cm −2 in solid oxide electrolysis cell mode at 700 °C with a given voltage of 1.3 V, respectively. In addition, both of two cells with LSN and PSN air electrodes present acceptable short-term stability under reversible operation condition. These encouraging results suggest that Ln1.2 Sr0.8 NiO4 could be suitable candidates of air electrodes in intermediate-temperature PC-RSOCs. Highlights: The Ln1.2 Sr0.8 NiO4 (Ln = La and Pr) were evaluated as the air electrodes of PC-RSOCs. The Ln1.2 Sr0.8 NiO4 exhibited favorable thermal and electrical properties. The cells with Ln1.2 Sr0.8 NiO4 electrodes showed good electrochemical performance. The cells with Ln1.2 Sr0.8 NiO4 electrodes presented acceptable short-term stability.